1072Mental health difficulties among adolescents in Ghana, coping mechanisms and the support systems: a mixed-methods study. (2nd September 2021) - Agbozo, Faith; Amobaa, Noella Dufie; Runge-Ranzinger, Silvia; Grys, Pauline
Abstract: Background: Despite their vulnerability, mental health of adolescents has received little attention in developing countries. We investigated the mental health difficulties faced by adolescents, their coping strategies and school-based support systems. Methods: Design was a convergent mixed-methods study. Quantitative data was collected : using the validated strengths and difficulties questionnaire to assess the mental health of 405 adolescents in four senior high schools (SHS) in the Techiman Municipality, Ghana. Qualitative data was collected through in-depth interview with 18 teachers and seven focused group discussions among 35 students. Adjusted odds ratio (OR) for mental health difficulties were estimated through ordinal logistic regression in Stata 14.2. Qualitative data were analysed by thematic content analysis using ATLAS.ti 7.1. Results: Over half (58.5%) experienced abnormalities related to peer (20.5%), emotional (16.3%), conduct (13.3%) and hyperactivity (3.0%) problems and prosocial behaviours (5.4%). Significant determinants were being female (OR = 2.27, 95% confidence interval [CI]:1.47-3.50), bullied (OR = 1.72, CI:1.07-2.75), domestic violence (OR = 1.87, CI:1.10-3.17), substance abuse (OR = 8.14, CI: 1.41-46.8), academic pressure (OR = 2.40, CI:1.30-4.42), and perceived poor performance (OR = 7.36 CI:2.83-19.16). Mental health difficulties were attributed to financial challenges, spiritual influences, intimate relationships, bullying, and domestic violence. Coping strategies included isolation, substance abuse and spiritual help. Guidance and counselling unit, the main support system, was ineffective due to issues with trust, confidentially, and qualified counsellors. Conclusions: As mental health difficulties were prevalent, school-based support systems, particularly guidance and counselling needs strengthening, including being manded by trained personnel. It is time to incorporate mental health education into school curricula. Key messages: Mental disorders among adolescents are common. While guardians and religious bodies are critical, many of the triggers occur in school necessitating mental health-friendly school environments.